Management of pulmonary ground-glass opacities: a position paper from a panel of experts of the Italian Society of Thoracic Surgery (SICT). (4th August 2020) - Lococo, Filippo; Luzzi, Luca; Cusumano, Giacomo; De Filippis, Antonio Fabillian; Pariscenti, Gianluca; Guggino, Gianluca; Rena, Ottavio; Davini, Federico; Grossi, William; Marulli, Giuseppe; Lococo, Achille; Cardillo, Giuseppe; et al.
Abstract: OBJECTIVES: A significant gap in our knowledge of how to manage pulmonary ground-glass opacities (GGOs) still exists. Accordingly, there is a lack of consensus among clinicians on this topic. The Italian Society of Thoracic Surgery (Società Italiana di Chirurgia Toracica, SICT) promoted a national expert meeting to provide insightful guidance for clinical practice. Our goal was to publish herein the final consensus document from this conference. METHODS: The working panel of the PNR group (Pulmonary Nodules Recommendation Group, a branch of the SICT) together with 5 scientific supervisors (nominated by the SICT) identified a jury of expert thoracic surgeons who organized a multidisciplinary meeting to propose specific statements ( n  = 29); 73 participants discussed and voted on statements using a modified Delphi process (repeated iterations of anonymous voting over 2 rounds with electronic support) requiring 70% agreement to reach consensus on a statement. RESULTS: Consensus was reached on several critical points in GGO management, in particular on the definition of GGO, radiological and radiometabolic evaluation, indications for a non-surgical biopsy, GGO management based on radiological characteristics, surgical strategies (extension of pulmonary resection and lymphadenectomy) and radiological surveillance. A list of 29 statements was finally approved. CONCLUSIONS: The participants at this national expert meeting analysed this challenging topic and provided a list of suggestions for health institutions and physicians with practical indications for GGO management.